Improving Georgia's energy security through natural gas exports from Iran - Maia Kapanadze; Seyed Mojtaba Mousavi (Revista Metropolitana de Ciencias Aplicadas)
Georgia’s energy security is increasingly vulnerable due to its reliance on Russian and Azerbaijani natural gas, exposing it to supply disruptions and geopolitical pressures. Iran, with the world’s second-largest natural gas reserves, offers a viable alternative to diversify Georgia’s energy mix. Despite U.S. and international sanctions on Iran’s energy sector, historical precedents—such as Iran’s emergency gas supply to Georgia in 2006—and innovative gas swap contracts, like the 2024 Turkmenistan deal, highlight the potential for energy cooperation. This article examines the strategic, economic, and diplomatic opportunities for Iran-Georgia collaboration, drawing on global examples of sanctions exemptions and academic literature to propose a framework for Georgia to secure Iranian gas imports legally. By leveraging regional infrastructure, diplomatic engagement, and creative trade mechanisms, Georgia can enhance its energy security, reduce dependence on dominant suppliers, and strengthen bilateral ties with Iran, contributing to regional stability in the South Caucasus.